Aristotle, Cicero and cosmopolitan political thought - Burns, Tony (2007)
This is a conference paper which compares and contrasts the views of Aristotle and Cicero in relation to cosmopolitan political thought. The paper focuses on the issue of the social and political 'identity' of the individual moral agent. It also distinguiishes between 'strong' and 'weak' versions of both 'cosmopolitanism' and 'communitarianism.' It argues that the views of Aristotle and Cicero are closer than is usually thought. Aristotle is more of a 'cosmopolitan' and less of a 'communitarian' thinker than is commonly supposed, whereas, on the other hand, Cicero is more of a 'communitarian' and less of a 'cosmopolitan' thinker.